Mouse Ovarian Tissue Vitrifiation: effects of exposure time to cryoprotective agent - Siripoon, Worawat; Sanmee, Usanee; Piromlertamorn, Waraporn; Vutyavanich, Teraporn (Biomedical Sciences and Clinical Medicine, 2016)
Objective The objective of this study was to compare the survival rate and growth rate of isolated preantral follicles from vitrifid/warmed mouse ovarian tissues with different exposure times to Vitrifiation Solution 2 (V2). Methods Mouse ovaries were divided into a control and four experimental groups. All four experimental groups were vitrifid and warmed with exposure times to V2 solution for 3, 5, 10 and 15-minutes. Preantral follicles were mechanically isolated from the vitrifid/warmed ovarian tissue and individually cultured in vitro in 10-μL drops of culture medium under paraffi oil. Follicle diameter was measured every two days for 12 days. Primary outcome measurements were the survival rate and growth rate of the isolated preantral follicles. Results Preantral follicles from vitrifid/warmed ovarian tissues that were exposed to V2 solution for fie and ten-minutes had the highest survival rates (73.20% and 72.17%, respectively). The three and fiteen-minute exposure groups had survival rates of only 65.37% and 56.55%, respectively. There was no difference in the mean diameter of the follicles during the fist eight days. On day ten, the mean follicular diameter of the fiteen-minute group was lower than the control group (p<0.001). On day 12, diameters of the three and fiteen-minute groups were lower than the control group (p=0.005 and p<0.001, respectively). The preantral follicles from the fie and ten-minute groups had growth rates comparable to the control group conclusion Exposure of mouse ovarian tissues to V2 solution for fie and ten-minutes yields the highest survival rate and growth rate of preantral follicles, while both longer and shorter exposures adversely affects the survival and subsequent development of preantral follicles.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />